Considering Watchmen: Poetics, Property, Politics : New edition with full color illustrations - Hoberek, Andrew, 1967- (Comics culture., 2017)
lan Moore and Dave Gibbons's Watchmen has been widely hailed as a landmark in the development of the graphic novel. It was not only aesthetically groundbreaking but also anticipated future developments in politics, literature, and intellectual property. Demonstrating a keen eye for historical detail, Considering Watchmen gives readers a new appreciation of just how radical Moore and Gibbons's blend of gritty realism and formal experimentation was back in 1986. The book also considers Watchmen's place in the history of the comics industry, reading the graphic novel's playful critique of superhero marketing alongside Alan Moore's public statements about the rights to the franchise. Andrew Hoberek examines how Moore and Gibbons engaged with the emerging discourses of neoconservatism and neoliberal capitalism, ideologies that have only become more prominent in subsequent years. Watchmen's influences on the superhero comic and graphic novel are undeniable, but Hoberek reveals how it has also had profound effects on literature as a whole. He suggests that Watchmen not only proved that superhero comics could rise to the status of literature--it also helped to inspire a generation of writers who are redefining the boundaries of the literary, from Jonathan Lethem to Junot Díaz. Hoberek delivers insight and analysis worthy of satisfying serious readers of the genre while shedding new light on Watchmen as both an artistic accomplishment and a book of ideas.